Titanium-indium oxy(nitride) with and without RuO2 loading as photocatalysts for hydrogen production under visible light from water - Kuo, Yenting; Frye, Clint D.; Ikenberry, Myles; Klabunde, Kenneth J. (My University, 2013)
Titanium-indium (oxy)nitride composite materials with and without RuO[subscript 2] loadings were produced by treating TiO[subscript 2]-In[subscript 2]O[subscript 3] mixed powders with ammonia at high temperature (700-850 °C) (Elemental analysis indicated an empirical formula of TiIn[subscript 0.029]O[subscript 0.63]N[subscript 1.4]). We have found that ammonolysis of TiO[subscript 2] to form Ti (oxy)nitride or In[subscript 2]O[subscript 3] to form In (oxy)nitride do not give composites active toward methanol-water under visible light, but TiO[subscript 2] and In[subscript 2]O[subscript 3] mixed together do give composites active toward methanol-water under visible light. Ti-In (oxy)nitride powders modified by surface loading with RuO[subscript 2] nanoparticles at 3 wt % achieves the highest H[subscript 2] evolution activity under visible light irradiation. The composite material did not react in the dark, but upon irradiation with visible light, the hydrogen production rate under illumination goes way up to 30 μmole∙h[superscript -1] and the turnover number shows that this is a photocatalytic reaction.
Keywords: H2 evolution; Photocatalysts; Ru co-catalyst; Titanium dioxide; Indium oxide